An experimental investigation of the air-side performance of crimped spiral fin-and-tube heat exchangers with a small tube diameter - Keawkamrop, Hawatchai; Asirvatham, Lazarus Godson; Dalkilic, Ahmet Selim; Ahn, Ho Seon; Mahian, Omid; Wongwi, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The performance of crimped spiral fin-and-tube heat exchangers (CSFTHXs) with a small tube diameter at a Reynolds number of 150 0-640 0 based on the tube's outer diameter is experimentally investigated. An important factor in this study is the small-diameter tubing, with an outer diameter of 9.53 mm. Cop-per tubes and aluminum fins are assembled as CSFTHXs. Test sections consist of a fin thickness of 0.5 mm, two tube rows, and various fin pitches and outer diameters of 3.18-6.35 mm and 23.0-28.5 mm, respectively. Hot water and fresh air are used as the working fluids. The effects of fin pitch and fin outer diameter on the heat transfer characteristics and friction factor (f) are also studied. The results show that the fin's pitch and outer diameter have little effect on the Nusselt number (Nu) and Colburn factor (j). On the other hand, they have a significant effect on the f . Furthermore, correlations between the Nu, j, and f for a CSFTHX with a small tube diameter are developed and proposed for designing heat exchangers in the thermal industry. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Crimped fin; Spiral fin; extended surface; Heat transfer; Heat exchanger; FRICTION CHARACTERISTICS; MULTIPASS PARALLEL; DRY-SURFACE; WAVY FIN; NUMBER; FLOW; PITCHES; ROWS; Thermodynamics; Engineering; Mechanics